Science Fiction in the Arab World: A Genre Still in the Cradle - BELKHARCHOUCHE, Malika (Journal of Human Sciences, 2010)
This paper is concerned with the status of science fiction literature in the Arab world; it seeks to examine the major causes and factors that have led the Arab countries to lag far behind the developed nations in the field of science fiction which has gained in the last few decades enormous popularity, and enjoys today a highly respectable academic status in the West with extraordinary amounts of books published in fiction, criticism, anthologies and even encyclopaedias. The paper examines the various conditions of life in the Arab societies related to politics, economy, science and technology, religion and language that have greatly contributed to the lack of interest in science fiction and the rareness of works in this field. After providing various definitions of science fiction, its constituting elements and its basic characteristics, the study also explores the different works of Arabic science fiction written in both earlier times and the modern period, and traces the attempts launched in the last few years to promote and develop science fiction writing in the Arab world.